Synthesis of tapioca starch/palm oil encapsulated urea-impregnated biochar derived from peppercorn waste as a sustainable controlled-release fertilizer - Sim, D.H.H.; Ivy Tan, Ai Wei; Lim, L.L.P.; Lau, E.T; Hameed, Bassim Hamid (Elsevier B.V., 2024)
Nutrient leaching and volatilization cause environmental pollution, thus the pursuit of developing controlled release fertilizer formulation is necessary. Biochar-based fertilizer exhibits slow-release characteristic, however the nutrient release mechanism needs to be improved. To overcome this limitation, the approach of applying encapsulation technology with biochar-based fertilizer has been implemented in this study. Black peppercorn waste was used to synthesize urea-impregnated biochar (UIB). Central composite design was used to investigate the effects of pyrolysis temperature, residence time and urea:biochar ratio on nitrogen content of UIB. The optimum condition to synthesize UIB was at 400 ◦C pyrolysis temperature, 120 min residence time and 0.6:1 urea:biochar ratio, which resulted in 16.07% nitrogen content. The tapioca starch/palm oil (PO) biofilm formulated using 8 g of tapioca starch and 0.12 μL of PO was coated on the UIB to produce encapsulated urea-impregnated biochar (EUIB). The UIB and EUIB pellets achieved complete release of nitrogen in water after 90 min and 330 min, respectively. The nutrient release mechanism of UIB and EUIB was best described by the Higuchi model and Korsmeyer-Peppas model, respectively. The improvement of water retention ratio of UIB and EUIB pellets was more significant in sandy-textural soil as compared to clayey-textural soil. The EUIB derived from peppercorn waste has the potential to be utilized as a sustainable controlled-release fertilizer for agriculture.